Northern Alaska / from a survey by E.W. Nelson, U.S.Signal Service shewing track of a sledge expedition made during 1878-1879; published for the proceedings of the Royal Geographical Society, 1882 - Nelson, Edward William, 1855-1934;United States. Army. Signal Corps (Royal Geographical Society (Great Britain), 1882)
Color 1:700,000